Hope Deferred: Theological Reflections on Reproductive Loss (Infertility, Stillbirth, Miscarriage) - Jones, L. Serene (Modern theology, 2001)
This essay examines the human experience of reproductive loss and grief surrounding infertility, miscarriage and stillbirth, in particular why such painful silences persist where one might least expect it; namely, in feminist communities and in churches. By bringing into conversation feminist theory and systematic theology on this topic, the author effectively crosses (and cross-fertilizes) the boundaries of two important sets of discourse with the hope of better understanding why painful silences persist concerning reproductive loss and what theological - in particular Trinitarian - resources are available to help the church think about the issue (both those who suffer this loss and the broader community who seeks to understand it).